Achieving Angular Superresolution of Control and Measurement Systems in Signal Processing (Advances in Systems Science and Applications, 2021)
Algebraic methods of processing data obtained by control and measurement systems to achieve angular superresolution are presented. The efficiency of using the methods in the formation of approximate images of objects at low signal-to-noise ratios is shown. The results of numerical experiments demonstrate the possibility of obtaining images with a resolution exceeding the Rayleigh criterion by 3-10 times. The robustness of the solutions obtained by the methods of algebraic exceeds many well-known approaches. The relative simplicity of the presented methods allows the use of inexpensive computing devices and perform real-time measurement processing.